Stone tools in the Ancient Near East and Egypt : ground stone tools, rock-cut installations and stone vessels from the prehistory to late antiquity - Squitieri, Andrea,; Eitam, David, 1948- (Archaeopress Near Eastern archaeology ;, 2019)
This text focuses on ground stone tools, stone vessels, and devices carved into rock across the Near East and Egypt from prehistory to the later periods. The aim is to explore all aspects of these tools and stimulate a debate about new methodologies to approach this material.